2013
DOI: 10.1101/sqb.2013.78.023283
|View full text |Cite
|
Sign up to set email alerts
|

The Zebrafish Guide to Tuberculosis Immunity and Treatment

Abstract: During the past 12 years, we have developed the zebrafish as a model for the study of tuberculosis pathogenesis and immunology. We have taken advantage of the optical transparency and the genetic and pharmacological tractability of the developing zebrafish to monitor infection in real time. Detailed information about the sequential interactions among the host and the pathogen, the cell types, and the molecules involved has yielded surprising insights into this ancient disease. We have identified a number of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 80 publications
0
50
0
Order By: Relevance
“…Zebrafish have also provided insights into human TB and raised questions that will be important to examine in human vaccine trials going forward [129]. In particular, a susceptibility factor involved in regulating TNF production (lta4h) was identified in a forward genetic screen in zebrafish, and a polymorphism of this gene was subsequently shown to confer susceptibility to TB in human populations [130, 131].…”
Section: The Path Forwardmentioning
confidence: 99%
“…Zebrafish have also provided insights into human TB and raised questions that will be important to examine in human vaccine trials going forward [129]. In particular, a susceptibility factor involved in regulating TNF production (lta4h) was identified in a forward genetic screen in zebrafish, and a polymorphism of this gene was subsequently shown to confer susceptibility to TB in human populations [130, 131].…”
Section: The Path Forwardmentioning
confidence: 99%
“…Third, the transparent larvae are ideal for imaging the early steps of the infection process in real time. Hence, zebrafish has earned its place of being a versatile tuberculosis model [1, 38, 39].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the protective effects of 2-DG were validated in vivo using M. marinum -zebrafish infection model, which is widely used to study the role of host immunity in mycobacterial pathogenesis [11,12,13]. Specifically, previous studies have revealed the crucial role of aerobic glycolysis in cytokines production [14,15,16].…”
Section: Introductionmentioning
confidence: 99%